Rediscovery and re(re)description of Scydmaenus kasuganus Franz, the only Japanese species of the subgenus Mascarensia Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2022)
Scydmaenus (Mascarensia) kasuganus Franz is the only nominal species of its subgenus known to occur in Japan. The only known specimen (holotype male) has been inadequately described, and later redescribed in an even more unfortunate way, after its fragile and unique aedeagus had been partly damaged. Therefore, the ‘redescription’ that not only contains even less useful details than the original description but also illustrations of only a portion of the aedeagus (the one which is the least diversified among Scydmaenus species), only decreased chances to identify this interesting species correctly. Newly collected specimens, including males found on Mount Kasuga ad Nara, the type locality, made it possible to redescribe S. kasuganus properly. A checklist of world Mascarensia species is given, and diagnostic characters of this problematic subgenus are discussed.